PENURUNAN TINGKAT ANSIETAS MAHASISWA DALAM MENYUSUN SKRIPSI MELALUI TERAPI GENERALIS ANSIETAS - Livana PH; Yulia Susanti; Dewi Arisanti (Jurnal Ilmu Keperawatan Jiwa, 2018)
DECREASING ANSIETAS LEVELS OF STUDENTS IN PREPARING THE SKRIPSI THROUGH ANSIETAS GENERALIS THERAPY ABSTRACTWhen students make thesis, they get several problems which cause anxiety. The anxiety that not handled soon will become emotional mental problem. The way to overcome anxiety is anxiety generalist therapy. The purpose of this study was determine the affect of anxiety generalist therapy with the student anxiety levels during making thesis. The design of this study used quasi experiment one group design pretest-posttest. The sample were 68 students who divided into 2 groups, first group is the students who hadn’t proposal examination and the second group is the students who had proposal examination. The result of Mann Whitney statistic test showed p value of both group is 0,000 (p<0,05) with heavy anxiety decreasing in the group which had not proposal examination (61,7%) and the group which had proposal examination the moderate anxiety is decreased (17,6%). The result of this study showed there are affect of anxiety generalist therapy to the student anxiety levels who makes thesis in the group student who hadn’t proposal examination and already proposal examination. anxiety generalist therapy can applied as independent on the students who anxiety when makes thesis and it’s used nurses to help anxiety of patient.